Inhaled Granulocyte-Macrophage Colony Stimulating Factor (GM-CSF) for Pulmonary Alveolar Proteinosis - Benali, Fahed (faculty of Basic Medical Science - Libyan International Medical University, 2020)
Pulmonary alveolar proteinosis is an uncommon lung disease with an accumulation of pulmonary surfactant within pulmonary alveoli that causes progressive respiratory insufficiency. The majority of the cases of pulmonary alveolar proteinosis are actually autoimmune that is associated with a high level of autoantibodies against granulocyte macrophage colony-stimulating factor (GM-CSF). These preformed autoantibodies, which effects the biologic activity of GM-CSF, impairing the clearance of surfactant and lead to the disease. Pulmonary alveolar proteinosis was previously treated with whole-lung lavage while the patient is under general anaesthesia. In this procedure, each lung is infused with up to 50 liters of saline to clear the surfactant sediment. Although this treatment improves lung function in most patients, but repeated treatments are required most of the time because of the re-accumulation of surfactant
Pulmonary alveolar proteinosis is a disease characterized by abnormal accumulation of surfactant within the lung, Most cases are autoimmune and are associated with an autoantibody against granulocyte-macrophage colony-stimulating factor (GM-CSF) that prevent clearing of pulmonary surfactant by alveolar macrophages. Pulmonary alveolar proteinosis may occur in three clinically distinct forms: congenital, secondary, or acquired. The congenital form comprises a heterogeneous group of disorders caused by mutations in the genes encoding surfactant protein B or C or the receptor for granulocyte–macrophage colony-stimulating factor (GM-CSF)